Study of Prevalance of QTc Interval Prolongation in ECG among Diabetic Population in DAE Hospital - Sitaraman, Sridevi (Journal of Neonatal Surgery, 2025)
This is the study of prevalence of QTc interval prolongation in ECG among diabetic population who presented to our institution (DEPARTMENTOFATOMICENERGYHOSPITAL). The prevalence of this abnormality is about 44 percent among diabetic population with raised hba1c levels. QTc interval is normally less than 450 ms for men and less than 460 ms for women. Hence by measuring the QTc interval in ECG we can assess the cardio vascular risk and sudden death in diabetic patients at an earlier stage for intervention and management. Study methodology- This is a retrospective study done in our institution from September 2024- February 2025 of 100 patients after obtaining ethical clearance and informed consent from all patients with DM on medications. Results- In our study out of 100 patients 80 were females and 20 of them were males. And about 55 out of 80 female patients were >60 years and 10 out of 20 male patients were >60 years. QTc prolongation was found in 16 females and 6 males out of which hba1c levels were >7 in 12 females and 4 males. Those patients on both OHA and insulin. And duration of diabetes was >10 years. Other risk factors like hyper tension, dyslipidemia, obesity were present in 35 females and 20 males. Hence QTc prolongation was more in females and other factors like duration of diabetes, increased hba1c attributed to it. Conclusion- Both type 1 and type 2 DM are risk factors of sudden cardiac death but type 1 patients there is more of genetic factors involved. In type 2 DM patients QTc prolongation is a cause of death because of ion cannel defects and ventricular arrythmias. Hence duration of diabetes hba1c levels and tight control of sugars with other risk factors contribute to increase of risk. So, early detection with simple ECG record will help in early management.